The Mythic Cyborgs of Croatian Oral Legends and the Fantasy GenreMitski kiborzi hrvatskih usmenih predaja i fantasy žanr - Marjanić, Suzana (Studia mythologica Slavica, 2011)
Within the above topic, our intention is to examine the links between animal and supernatural female (mora – fairy – witch) phenomena in Croatian oral legends. Namely, certain characteristics of the mora and witches can be defined by the term zoopsychonavigation (navigation of the soul in an animal form), and we can differentiate three types of zoopsychonavigation – zoometempsychosis, zoometamorphosis as well as witches’ riding, or flying on astral animal vehicles. Further, we will also consider within this topic the zoomorphic characteristics of fairies as mythic cyborgs, who often have feet (hoofs/ungulae) like donkeys, horses, goats and oxen within the Croatian folklore imaginary, thereby creating the iconographic paradox of the fairy’s body – the upper half of the body is ornithomorphic (with wings) and the lower half of the body is tellurian (with hoofed feet). In brief, we shall endeavour to research the transfer of the animal characteristics of mythic beings as mythic cyborgs (cf. Donna J. Haraway, Cyborg Manifesto: Science, Technology, and Socialist-Feminism in the Late Twentieth Century, 1985) from classic myths and oral legends into fantasy films.